Influences of intergrowth structure construction on the structural and electrical properties of the BBT-BiT ceramics - Wang, Yuying; Zheng, Deyi; Mao, Runyu; Wang, Xu (Frontiers in Chemistry, 2022)
Bismuth Layer Structured Ferroelectrics (BLSFs) have always been an important research direction of high Curie temperature piezoelectrical ceramics, and the construction of intergrowth structure has been considered as an effective method to improve the electric properties of BLSFs. There are many literatures about intergrowth structure improving electrical performance, but few reports analyze the influence of the construction of intergrowth structure on the internal defects and electrical properties in BLSFs. In this study, (1-x) BaBi4Ti4O15 - x Bi4Ti3O12 ceramic samples with intergrowth bismuth layer structure were fabricated by a conventional solid-state reaction method, and the mechanism of the influence of intergrowth structure construction on the structure and electrical properties of BLSFs has been discussed. The crystal structure, phase composition, microstructure, dielectric and piezoelectric performance, relaxation behavior and AC conductivity of ceramic samples were systematically investigated. It has been found that the construction of intergrowth structure can significantly inhibit the generation of oxygen vacancies. The concentration of the oxygen vacancies plays an important role, and its reduction will lead to the inhibition of grain growth and the increase of the relaxation activation energy of ceramics. In addition, the intergrowth structure construction also affects the symmetry of ceramics in the c-axis direction, thus affecting the electrical properties of ceramics.